Pemanfaatan Class Point untuk Meningkatkan Keterampilan Berpikir Kritis Siswa dalam Pembelajaran IPA di SMP Negeri 259 Jakarta - Elvina Elvina (International Forum of Researchers and Lecturers, 2025)
This study aims to enhance students' critical thinking skills in Science learning at SMP Negeri 259 Jakarta through the utilization of the Class Point application. The research employs the Classroom Action Research (CAR) method conducted in three stages: pre-cycle, cycle I, and cycle II, with 35 eighth-grade students as the subjects. The results show that the use of Class Point significantly improved students' critical thinking skills, reflected by the increase in the class average score from 68.2 in the pre-cycle to 82.1 in cycle II. The students' engagement also increased from 55% in the pre-cycle to 89% in cycle II. Thus, the use of Class Point proves to be an effective alternative in enhancing students' critical thinking abilities in Science learning.